Analysis of Traffic Accident Correspondence in Central Java Province - Regita Nurul Fitriani; Nur Khasanah (Jurnal Fourier, 2022)
The transportation sector can facilitate and accelerate human activities. However, the development of the transportation sector has a negative impact that causes traffic jams and causes traffic accidents. Traffic accidents can cause fatalities which are divided into 3 categories, namely minor injuries, serious injuries, and death. This study aims to analyze the relationship between district or city variables in the province of Central Java with the status of the category of accident victims that occurred in 2019 – 2020. This study uses R Studio software as a tool to facilitate data analysis. The method used is correspondence analysis by representing the results obtained through the correspondence graph that is formed. In two consecutive years, accidents were dominated by victims of the minor injury status category in the city of Surakarta with a percentage of 94,7% in 2019 and 94,6% in 2020.